Self-Confidence pada Anak yang Mengalami Fatherless - Desi Riska Sandra Devi; Siti Nur Alfina Wandayanti; Bella Dwi Ayu Saputri; Icha Fazira Anwar; Dhelia Kumala Amalianti; Faruq Faruq (Universitas Kristen Maranatha, 2025)
The issue of fatherless has become an international problem, including in Indonesia. Fatherless itself is a condition that covers a variety of circumstances, including the absence of a physical or emotional role of a father. This study aims to investigate self-confidence in children who experience fatherless and the impact of fatherless in children. The method used in this research is a qualitative research method with a phenomenological approach. The data collection technique used was interviews involving 5 participants with different causes of fatherlessness, some due to divorced parents, dead fathers, and fathers who did not carry out their full roles and responsibilities. The data analysis technique in this study used Interpretative Phenomenologycal Analisyst. The results showed that fatherless has several impacts on children's self-confidence, including feelings of insecurity, impaired socialization, and barriers to self-expression. In addition, it was also found that 4 childrens (80%) had a sense of uncertainty in their abilities such as feelings of doubt and difficulty in expressing themselves. While 1 child (20%) felt confident in their abilities and did not give up on their failure. This study provides information about the description of children's self-confidence through parental care, especially fathers in the family.